Indirect morphological analysis of particles in polymer particle composites via non-destructive permittivity measurements. (5th January 2019) - Mühlstädt, Mike; Arras, Matthias M.L.; Zimmer, Philip; Jandt, Klaus D.; Bossert, Jörg
Abstract: Polymers with special properties (e.g. electrical, optical or mechanical) are often obtained via the addition of fillers. The composites' final properties rely on the preservation of these fillers during blending, which is, in particular, challenging for high aspect ratio particles, like shear-sensitive flaky particles (ssFP). Thus, in cases of ssFP off- or in-line monitoring is indicated. This study addresses the lack of suitable non-destructive monitoring methods appropriate for ssFP possessing a thickness below 1 μ m and an area equivalent diameter of several 10 μ m . An elegant method was developed to validate the integrity of ssFP within composites, which is based on the measurement of the composites' permittivity and applying precise micro-structure property correlations to indirectly determine the fillers' morphological features. The main hypothesis tested was that a reduction of the particles aspect ratio by a factor of larger than 5 can be detected by the measurement of the composites' permittivity. In this study, polyethylene or epoxy resin were blended with the mica-based ssFP Iriodin 153 which features a mean area equivalent diameter of 42 μ m and an average thickness of about 1 μ m . The micro-structure property correlation presented by G. Ondracek [Z. f. Werkstofftechnik, 8:280-287, 1977] provided the necessary theoretical backbone to indirectly infer geometrical changes to the ssFP from permittivity measurements of the composite. An excellent match was obtained between the indirectly (permittivity measurements) and the directly (ashing of matrix and subsequent scanning electron microscopy) determined particles' aspect ratios which related directly to the particles' area equivalent diameter because the thickness of the particles was almost constant. This preliminary study established the presented technique as a promising non-destructive test method to monitor the integrity of ssFPs embedded in polymers. In principle this technique is adaptable for in-line process monitoring.